FEATURES OF WORKING WITH YOUNG MAN VOICES IN THE SYSTEM OF SECONDARY PROFESSIONAL MUSIC AND PEDAGOGICAL EDUCATION - Солдаткина, Ольга; Маруфенко, Елена (SWorldJournal, 2020)
The authors consider theoretical and practical aspects of working with young man voice in the system of secondary professional musical-pedagogical education, the consider relevance of such work, psycho-pedagogical and age characteristics age College stud